Synthesis of pH-Sensitive and Self-Fluorescent Polymeric Micelles Derived From Rosin and Vegetable Oils via ATRP - Yu, Juan; Xu, Chaoqun; Lu, Chuanwei; Liu, Qian; Wang, Jifu; Chu, Fuxiang (Frontiers in Bioengineering and Biotechnology, 2021)
Preparation and application of sustainable polymer derived from renewable resources are of great significance. The aim of this study is to synthesize a kind of sustainable polymeric micelles from rosin and vegetable oils via atom transfer radical polymerization (ATRP) and to investigate the doxorubicin delivery properties of these micelles. Dehydroabietic acid based poly lauryl methacrylate (DA-PLMA) with narrow PDI of 1.13 was prepared in a well-controlled process using rosin as ATRP initiator. Thereafter, carboxylic groups were introduced to form poly methacrylic acid (PMAA) moieties in DA-PLMA polymers via acid hydrolysis. The resulted DA-PLMA-PMAA could self-assemble in water to form pH-dependent polymeric micelles with a diameter of ~65nm and PDI as low as 0.105. Owing to the existence of rosin, DA-PLMA-PMAA micelles also showed self-fluorescence properties. In addition, Dox-loaded micelles were prepared in aqueous solution with the drug loading capacity as high as 16.0 %, and showed sustained-release characteristics. These results demonstrate great promise for designing polymeric micellar from rosin and vegetable oils.